Noninvasive Ventilation in Obese Subjects After Acute Respiratory Failure. - Bry, Charlotte; Jaffré, Sandrine; Guyomarc'h, Béatrice; Corne, Frédéric; Chollet, Sylvaine; Magnan, Antoine; Blanc, François-Xavier (Respiratory Care, 2018)
INTRODUCTION: Noninvasive ventilation (NIV) has been widely used to treat acute respiratory failure in obese patients. Criteria that could help clinicians to decide whether they should continue to use NIV after such an initial episode remain unclear. Our retrospective study aims to analyze characteristics of subjects receiving long-term NIV after an initial hospitalization for acute respiratory failure. METHODS: From January 2011 to December 2012, 77 obese adults were admitted in the ICU of the respiratory disease department in Nantes University Hospital in France. After discharge, adherence, body mass index (BMI), and arterial blood gases were assessed or measured at 6 months and 12 months. RESULTS: In all, 53 subjects were analyzed, including 62% who were admitted for idiopathic acute hypercapnic respiratory failure. Mean BMI was 42 ± 11 kg/m². Failure of NIV occurred in 10% cases in the ICU. At the end of the hospital stay, 34 subjects were discharged with NIV at home. They had higher BMI and higher initial inspiratory positive airway pressure than those who were not ventilated at home. During follow-up, BMI, P..., and bicarbonate rate significantly decreased. At 12 months, 4 subjects were not ventilated anymore after a mean duration of 6 ± 4.2 months of ventilation. Adherence was correct in 86%, with a mean use of 7 ± 3.1 h/d. Adherent subjects had better adherence at 1 month, a lower forced vital capacity, a higher bicarbonate rate, and a higher NIV breathing frequency when compared to subjects with poor adherence. CONCLUSIONS: Subjects with the most severe obesity or who experienced the most difficult initial ventilation were more likely to receive long-term NIV after initial management of acute respiratory failure in the ICU. In those subjects, long-term NIV at home was effective and well tolerated.